Strategi Bimbingan Kelompok Dengan Teknik Self Management Untuk Meningkatkan Motivasi Belajar Siswa Kelas XI SMA Negeri 6 Pandeglang Tahun Ajaran 2025/2026 - oktaviani; Devi Nurul Fikriyani; Muhamad Ikhsan (Advice: Jurnal Bimbingan dan Konseling, 2025)
Learning motivation is the drive from both internal and external sources of students that makes them enthusiastic about learning, striving to achieve achievements, and able to overcome obstacles in the learning process. The research design used in this study is the "One Group Pretest-Posttest Design." This study aims to determine the effect of group guidance strategies using self-management techniques on increasing the learning motivation of eleventh-grade students at SMA Negeri 6 Pandeglang for the 2025/2026 academic year. The population in this study consists of eleventh-grade students at SMA Negeri 6 Pandeglang, sample in this study consisted of 79 students who were given a learning motivation questionnaire; the selected students for the experimental group then received treatment with group guidance using self-management techniques. The data collection technique used was a learning motivation questionnaire prepared by the researcher, while the data analysis technique employed normality tests, homogeneity tests, and T-tests. The research results showed that after the treatment, there was a difference in the average pretest and posttest scores. Hypothesis testing using the T-test results yielded a sig (2-tailed) value of 0.001 < 0.05, which means Ha is accepted and Ho is rejected. This proves that there is a significant difference in learning motivation before and after the treatment. Therefore, students' learning motivation increased after being provided with group guidance services using the self-management technique to enhance students' learning motivation. Keywords: Learning Motivation, Group Guidance, Self Management